Experimental investigation of concentration yields of liquid phase exfoliated graphene in organic solvent media - Arifutzzaman, Abul; Ismail, Ahmad Faris; Yaacob, Iskandar Idris; Alam, Md Zahangir; Khan, Ahsan Ali (IOP Publishing Ltd, 2019)
The main purpose of this work is to experimentally investigate the concentration yields of exfoliated Graphene in organic solvents with the variation of different centrifugation speeds (rpm). Graphene was effectively fabricated by one of the most convenient chemical processing approach liquid-phase exfoliation (LPE) of graphite in two different organic solvent N-Methyl-2-Pyrrolidone (NMP) and N, N-dimethylformamide (DMF). After exfoliation separated supernatant dispersions were preserved into the other tube as product. Similar procedure was repeated with same parameter and same graphite for both of the solvents. FESEM analyses of the exfoliated Graphene samples revealed the presence of few layers of Graphene flakes stacking. Analysis of the Raman spectrum of the samples it was revealed that the precursor graphite flakes was converted to Graphene sheets. Concentrations of graphene suspensions in both solvents were measured from separately prepared standard graphs using Beer’s law with the aid of UV-vis absorbance spectroscopy. Estimated exfoliated graphene concentration was acquired higher for lower centrifugation (rpm) for both of the solvent. It was also seen that for the same rpm concentration of Graphene was higher in NMP than that of in DMF.